DRAWINGS AFTER THE NOVELS OF AMON MUKHTOR (Scientific journal of the Fergana State University, 2024)
The article describes the role of the works of Amon Mukhtar in the development of Uzbek prose of the 20th-21st centuries. The themes and characters of the author's novels, art, and sources of influence are analyzed. His role in the development of the novel is explained.